Mass Balance Model with Donnan Equilibrium Accurately Describes Unusual pH and Excipient Profiles during Diafiltration of Monoclonal Antibodies. Issue 7 (20th May 2019) - Baek, Youngbin; Singh, Nripen; Arunkumar, Abhiram; Borwankar, Ameya; Zydney, Andrew L.
Abstract : There is extensive experimental data showing that the final pH and buffer composition after protein diafiltration (DF), particularly with monoclonal antibodies, can be considerably different than that in the DF buffer due to electrostatic interactions between the charged protein and the charged ions. Previous models for this behavior have focused on the final (equilibrium) partitioning and are unable to explain the complex pH and concentration profiles during the DF process. The objective of this study is to develop a new model for antibody DF based on solution of the transient mass balance equations, with the permeate concentrations of the charged species evaluated assuming Donnan equilibrium across the semipermeable membrane in combination with electroneutrality constraints. Model predictions are in excellent agreement with experimental data obtained during DF of both acidic and basic monoclonal antibodies, with the protein charge determined from independent electrophoretic mobility measurements. The model is able to predict the entire pH/histidine concentration profiles during DF, providing a framework for the development of DF processes that yield the desired antibody formulation. Abstract : A new model for the pH and excipient profiles throughout a diafiltration (DF) process is developed based on the numerical solution of the transient mass balances coupled with Donnan equilibrium and electroneutrality constraints. The model is in excellent agreement with experimental results for the pH and excipient concentrations during DF with both acidic and basic monoclonal antibodies, providing a framework that can be used for the design and optimization of DF processes for the formulation of therapeutic proteins.